Omega 3 supplementation reduces C-reactive protein, prostaglandin E2 and the granulocyte/lymphocyte ratio in heavy smokers: An open-label randomized crossover trial - Elisia, Ingrid; Yeung, Michelle; Kowalski, Sara; Wong, Jennifer; Rafiei, Hossein; Dyer, Roger A.; Atkar-Khattra, Sukhinder; Lam, Stephen; Krystal, Gerald (Frontiers in Nutrition, 2022)
Abstract Objectives: Given the current controversy concerning the efficacy of omega 3 supplements at reducing inflammation, we evaluated the safety and efficacy of omega 3 on reducing inflammation in people with a 6-year lung cancer risk >1.5% and a C reactive protein (CRP) level >2 mg/L in a phase IIa cross-over study. Materials and Methods: Forty-nine healthy participants ages 55 to 80, who were still smoking or had smoked in the past with ≥30 pack-years smoking history, living in British Columbia, Canada, were randomized in an open-label trial to receive 2.4 g eicosapentaenoic acid (EPA) + 1.2 g docosahexaenoic acid (DHA)/day for 6 months followed by observation for 6 months or observation for 6 months first and then active treatment for the next 6 months. Blood samples were collected over 1 year for measurement of plasma CRP, plasma and red blood cell (RBC) membrane levels of EPA, DHA and other fatty acids, Prostaglandin E2 (PGE2), Leukotriene B4 (LTB4) and an inflammatory marker panel. Results: Twenty one participants who began the trial within the active arm completed the trial while 20 participants who started in the control arm completed the study. Taking omega 3 resulted in a significant decrease in plasma CRP and PGE2 but not LTB4 levels. Importantly, the effect size for the primary outcome, CRP values, at the end of the intervention relative to baseline was medium (Cohen's d = .56). DHA, but not EPA levels in RBC membranes inversely correlated with PGE2 levels. Omega 3 also led to a significant reduction in granulocytes and an increase in lymphocytes. These high-dose omega 3 supplements were well tolerated, with only minor gastrointestinal symptoms in a subset of participants. Conclusion: Omega 3 fatty acids taken at 3.6 g/day significantly reduce systemic inflammation with negligible adverse health effects in people who smoke or have smoked and are at high risk of lung cancer.